Volume 3: Coal, Biomass and Alternative Fuels; Cycle Innovations; Electric Power; Industrial and Cogeneration; Organic Rankine 2016
DOI: 10.1115/gt2016-57988
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Zero-Emission Graz Cycle for Hydrogen Combustion and Investigation of Its Part Load Behaviour

Abstract: A modern energy system based on renewable energy like wind and solar power inevitably needs a storage system to provide energy on demand. Hydrogen is a promising candidate for this task. For the re-conversion of the valuable fuel hydrogen to electricity a power plant of highest efficiency is needed. In this work the Graz Cycle, a zero emission power plant based on the oxy-fuel technology, is proposed for this role. The Graz Cycle originally burns fossil fuels with pure oxygen and offers efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Neglecting the investment cost, the hydrogen price should be in the range 0.8-3 €/kg for competitiveness with other electricity generation sources. Note that recent research has shown that energy efficiency up to 68% could be achieved for electricity generation with a hydrogen combustion power plant based on an adapted Graz cycle [49]. Moreover, in the case of co-generation of heat and electricity, the efficiency could increase to 85% which would make a higher price acceptable.…”
Section: Light Industrymentioning
confidence: 99%
“…Neglecting the investment cost, the hydrogen price should be in the range 0.8-3 €/kg for competitiveness with other electricity generation sources. Note that recent research has shown that energy efficiency up to 68% could be achieved for electricity generation with a hydrogen combustion power plant based on an adapted Graz cycle [49]. Moreover, in the case of co-generation of heat and electricity, the efficiency could increase to 85% which would make a higher price acceptable.…”
Section: Light Industrymentioning
confidence: 99%